2007
DOI: 10.1007/s11243-007-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and biological activity of the nickel(II) complex of 2,6-diacetylpyridinedihydrazone

Abstract: A complex of Ni II with 2,6-diacetylpyridinedihydrazone (L) towards nickel(II) has been prepared and characterized by means of elemental analyses, IR, electronic spectra and single crystal X-ray analyses. [NiL 2 ](NO 3 ) was crystallized in the tetragonal space group P-4 21 c. The complex exhibits the expected coordination sphere with six nitrogen atoms coordinated to the central Ni II with a deformation from pseudo-octahedral geometry. Antimicrobial activities of the ligand and its complex were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Due to the great flexibility and diverse structural aspects, a wide range of Schiff bases have been synthesized and their complexation behaviour studied [3]. They have been synthesised from a variety of compounds, such as amino thiazoles, 2-hydroxy-1-napthal aniline, amino sugars, aromatic aldehydes, isatin, the triazole ring, thiosemicarbazides, amino acids, pyrazolone, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the great flexibility and diverse structural aspects, a wide range of Schiff bases have been synthesized and their complexation behaviour studied [3]. They have been synthesised from a variety of compounds, such as amino thiazoles, 2-hydroxy-1-napthal aniline, amino sugars, aromatic aldehydes, isatin, the triazole ring, thiosemicarbazides, amino acids, pyrazolone, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished by the condensation of reactive carbonyls of aldehyde or ketone with amino groups on chitosan [19]. In particular, Schiff bases of 2,6-diacetylpyridine and its metal complexes are preferred because of their excellent physicochemical characteristics in coordination chemistry [20,21].…”
Section: Q2mentioning
confidence: 99%
“…For  a few decades now, hydrazones are interesting field of research due to their good chelating properties (Kitaev & Buzykin, 1974;Kogan et al, 1990;Watanabe et al, 2018), but the pharmacological activity, as well. The research has shown that some compounds from this group have promising antibacterial, antifungal and antitumor activities (Ainscough et al, 1998;Avaji et al, 2009;Azaz et al, 2007;Mahalingam et al, 2008;Wang et al, 2007), and some of their derivatives are suggested as reagents for the treatment of genetic and neurodegenerative disorders, such as thalassemic syndrome and Alzheimer's (Armstrong et al, 2003;Bernhardt et al, 2007;Buss et al, 2005;Donnelly et al, 2008). Besides, some of these compounds are used as highly sensitive analytical reagents, luminescent probes and molecular sensors (ávila Terra et al, 2002;Bakir et al, 2008;Basu et al, 2007;Pinto et al, 2004;Sreeja et al, 2003).…”
Section: Introductionmentioning
confidence: 99%